Aquananotechnology : Global Prospects - Reisner, David Evans; Pradeep, T. (New York : CRC Press, 2015)
"Nanotechnology is finding numerous uses in the water industry, including high surface area filtration media, membranes for desalination plants, and fundamental new methods for desalination. This book provides a comprehensive overview from a global perspective, the latest research, and developments in the use of nanotechnology for water purification and desalination methods. It demonstrates the role of nanotechnology in water treatment"--
Keywords: Water -- Purification -- Materials; Nanostructured materials -- Environmental aspects; Nanofiltration